Analisis Faktor Yang Mempengaruhi Tingkat Partisipasi Anggota Koperasi (Studi Kasus: KPRI-SEDAR) - Amalia Indah Kartika; Zulkarnain Lubis; Faoeza Hafiz Saragih (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
Member participation is the participation of members in exercising their rights and obligations mentally or emotionally to improve or maintain or achieve cooperative goals. This study aims to determine the effect of member participation on satisfaction, level of trust, business environment, service quality, and motivation of members. This research was conducted at the Cooperative of the Republic of Indonesia Employees Percut Sei Tuan. Sampling in this study uses a Simple Random Sampling method. The number of samples examined in this study is 40 samples of cooperative members. This study uses the method of Classical Assumption Test and Multiple Linear Regression. The results of this study indicate The coefficient of RÂ² value of 0.454 can be interpreted that 45.5% participation of members can be influenced by these variables,and the results study indicateÂ  that there are significant variables of Member Satisfaction, and where other variables such as the level of trust, business environment, service quality and member motivation there are no adherence to level participation level variables of member at the Cooperative of the Republic of Indonesia Employees.